Port Closure Due to the Covid-19 Pandemic in the Law of Carriage of Goods By Sea and Unidroit Principles of International Commercial Contracts - Misridaputri*, Syifa Salsabila; Ikhwansyah, Isis; Trisnamansyah, Purnama (Riwayat: Educational Journal of History and Humanities, 2023)
Port closure as an effort to slow the spread of the Covid-19 virus has had various impacts, such as port congestion which has led to delays and drastically increased transportation costs. This study examines the impacts caused by port closures and legal remedies that can be taken based on international sea transport law. Losses due to port closures cannot be borne by the carrier based on the conventions of sea shipping law as long as the carrier can prove that the fault was not his own. The closure of the port can be categorized as a hardship, in which there are fundamental changes that affect the agreement, namely the increase in shipping costs and delays. efforts that can be made based on the UPICC are renegotiation, and if it fails, the parties can seek a dispute settlement through the courts. In implementing the agreement, the parties must prioritize the principle of good faith and prove that the losses incurred and losses did not originate from themselves.